O compromisso social dos analistas do comportamento: caracterização e exame de publicações em periódicos brasileiros da área - Fink, Júlia Daher (2014)
Although Skinner created a science which serves as an analytical and pragmatical tool towards relevant changes for the improvement of human living conditions and dedicated part of his work discussing problems of Western culture, the author and behavior analysis are accused to be in service of reactionary interests. In order to investigate Brazilian researchers' approach to social issues, this study examined sixty-four articles available in four specific behavior analysis journals: Revista Brasileira de Terapia Comportamental e Cognitiva (RBTCC), Revista Brasileira de Análise do Comportamento (REBAC), Revista Psicolog (Psicolog) and Perspectivas em Análise do Comportamento (Perspectivas). To ensure that relevant articles to the topic would be selected, a list of key terms was extracted from government projects, OSCIPs' listing and social movements. Articles were categorized according to type, subject, population and setting, but also according to questions that verified important points about the behavior analysts social commitment. Results showed that few texts (15.6%) are related to social problems. Although application reports were prevalent, a wide range of text types was found. The most addressed subject was education. The majority of application reports and basic researches used students or individuals with developmental disabilities or disorders. The latter noted as a longstanding interest in behavior analysis. Considering social commitment to be a series of behaviors, we note that the behavior analyst has shown major social concerns, like conducting research intended to enhance technology in educational practice in low-income populations. In the same way we found reports where interventions were made to train the population in order to maintain positive results even in the absence of the researcher. On the other hand, we found reports in which researchers disregarded population demands and reports with weak experimental control